Azospirillum inoculation effects on growth, product quality and storage life of lettuce plants grown under salt stress - Fasciglione, Gabriela (2015)
Recent results have shown that Azospirillum-inoculated lettuce seeds yield a higher number of transplanted plants with superior traits than non-inoculated controls grown with and without saline stress. However, little available information on the possibility that Azospirillum could improve nutritional and quality market parameters on plants grown under saline conditions and extend life storage has prompted us to explore this issue. In this work, seed inoculation with Azospirillum not only promoted higher biomass but also improved lettuce quality when plants were grown under salt-stress conditions. Compared to non-inoculated controls, higher ascorbic acid content was accompanied by a lower oxidation rate in Azospirillum-inoculated plants. In addition, better overall visual quality was linked to higher chlorophyll content, hue, Chroma, L and lower browning intensity. While the beneficial effects of Azospirillum inoculation were more evident at harvest, some of these continued thereafter. Compared to non-inoculated controls, higher aerial biomass, chlorophyll and ascorbic acid content, better overall visual quality, hue, Chroma and antioxidant capacity, and a lower browning intensity were observed after storage in Azospirillum-inoculated plants grown under salt stress. These results suggest that seed inoculation with Azospirillum not only could improve freshly product quality but also extend storage life in lettuce grown under salt stress.